DEVELOPMENT OF A DECISION SUPPORT SYSTEM FOR STRATEGIC BUSINESS LOCATION SELECTION USING MOORA METHOD - Riski Zulkarnain; Mundzir, Mundzir; Sri Winar (Universitas Mulia, 2022)
The key to launching a successful business is securing a strategic location, as optimal results hinge on this crucial factor. Today, there are numerous potential business locations available, such as areas currently undergoing development or residential complexes in proximity to major highways. Considering these factors empowers businesses to make well-informed decisions about whether a particular location is truly strategic for their ventures. When business owners make location-related decisions, they must carefully assess several aspects, such as the size and dimensions of the building, the presence of competitors nearby, and the rental or selling prices. By evaluating these criteria, businesses can identify strategic locations and minimize the risks of potential losses when establishing their operations. Acquiring a strategic business location yields numerous advantages and significantly reduces startup losses. To achieve this, the research presented in this journal employs the MOORA (Multi-Objective Optimization on The Base Method of Ratio Analysis) research method, which serves as both a means to determine strategic business locations and a strategy for enhancing overall business performance.